2021
DOI: 10.1016/j.cell.2021.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Spatially organized multicellular immune hubs in human colorectal cancer

Abstract: Highlights d A scRNA-seq study reveals shared and distinct features of human MMRd and MMRp CRC d Co-variation of single-cell transcriptional programs across specimens predicts immune hubs d A myeloid-rich inflammatory hub is identified below the colonic lumen in human CRC d CXCR3-ligand+ cells form foci with activated T cells in human MMRd CRC

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
320
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 372 publications
(451 citation statements)
references
References 93 publications
(100 reference statements)
27
320
1
Order By: Relevance
“…Furthermore, this study showed tumour-specific T cell responses, with enrichment and clonal expansion of pro-inflammatory CXCL13 + BHLHE40 + TH1-like cells in tumours with microsatellite instability, but moderate enrichment for Th17 cells in those with microsatellite stability 100 . The enrichment of CXCL13 + T cells in tumours with high mutational burden was supported by a second scRNAseq study and offers a possible explanation for why this patient cohort responds better to checkpoint blockade therapy 100 , 101 . Together these studies highlight how scRNAseq can assist in understanding the complexity of intestinal diseases and the nuanced involvement of cell types and states in disease progression and control.…”
Section: Heterogeneity and Plasticity Of Intestinal Immune Cellsmentioning
confidence: 68%
“…Furthermore, this study showed tumour-specific T cell responses, with enrichment and clonal expansion of pro-inflammatory CXCL13 + BHLHE40 + TH1-like cells in tumours with microsatellite instability, but moderate enrichment for Th17 cells in those with microsatellite stability 100 . The enrichment of CXCL13 + T cells in tumours with high mutational burden was supported by a second scRNAseq study and offers a possible explanation for why this patient cohort responds better to checkpoint blockade therapy 100 , 101 . Together these studies highlight how scRNAseq can assist in understanding the complexity of intestinal diseases and the nuanced involvement of cell types and states in disease progression and control.…”
Section: Heterogeneity and Plasticity Of Intestinal Immune Cellsmentioning
confidence: 68%
“…Like CD8 T cells, CD4 T cells upregulated CXCL13 in irColitis. CXCL13-expressing T cells have also been described across many different cancer types including colon cancer, where they comprise larger hubs that are relatively depleted of B cells but contain CXCL10/11-expressing myeloid and malignant cells and are predictive of immunotherapy responsiveness (Litchfield et al 2021;Pelka et al 2021). Thus, in the context of ICI therapy, CXCL13 may serve as a homing signal for cell types other than CXCR5 expressing B cells.…”
Section: Discussionmentioning
confidence: 99%
“…Protein immunofluorescence staining for CD8A, CD68, FoxP3, PD-1, PD-L1, and PanCK was performed using the Motif PD-1/PD-L1 panel (Akoya Biosciences OP-000001) on a Leica Bond Rx instrument (Leica Biosystems) per manufacturer's protocol. Mixed RNAscope in situ hybridization and antibody antigen retrieval and staining was performed with RNAscope probes to CXCL13, CXCL10/11, IFNG, and CD3E and antibody to panCK on a Leica Bond Rx instrument using the RNAscope LS multiplex Fluorescent v2 Assay combined with Immunofluorescence protocol (Advanced Cell Diagnostics (ACD) 322818-TN) as described previously (Pelka et al 2021). The only two variations from the written protocol were (1) an open wash dispense after the peroxide step and (2) DAPI (Sigma D9542) was dispensed twice at the end of the protocol at a concentration of 1 µg/mL.…”
Section: Rna and Immunofluorescence Microscopymentioning
confidence: 99%
“…Although less is known about the direct role of ADAM12 in CPI response, it is highly expressed by cancer associated fibroblasts CAFs-as shown through single cell sequencing studies and bulk tumor profilingas a driver of feed forward TGF-β signaling, has been shown to act as a T cell co-stimulatory molecule expressed on some regulatory T cells, and has been identified in a signature of negative response to ICI in melanoma [52][53][54][55][56][57] . Of note, in colorectal cancer, where single cell sequencing demonstrated high ADAM12 expression in CAFs 58 , as well as urothelial carcinoma, TGF-β signaling from CAFs has been shown to drive T cell exclusion, a hallmark of low response to ICI [59][60][61][62][63] . Taken together, these results support additional investigation into a potential mechanistic role for ADAM12 in ICI resistance, as well as demonstrate the complementary nature of the integrative biomarkers in the IRS model, which integrates measurement of tumor neo-antigenicity (TMB), with quantification of key tumor and TME biomarkers.…”
Section: Discussionmentioning
confidence: 99%